Enhance e-learning system performance with a cloud and crowd-oriented approach. (2018) - Tseng, Chun-Hsiung; Huang, Ching-Lien; Chen, Yung-Hui; Chuang, Chu-Chun; Syu, Han-Ci; Jiang, Yan-Ru; Tsai, Fang-Chi; Su, Pin-Yu; Chen, Jun-Yan
There are several e-learning systems focusing on the flipped classroom concept. The basic concept of flipped classroom is to have students learn by themselves. Once the background learning stage is performed outside of the class time, tutors have free time to lead students to participate in higher-order thinking. However, as shown in the report of Ash (2012), the performance of the flipped classroom method is arguable. Our survey shows that the contents offered by most modern e-learning systems are relatively static. Considering how fast new information appears on the web, creating content requires effort. The work load of our teachers is already heavy, so expecting teachers to update contents very frequently is not practical. Besides, crowd intelligence is usually considered helpful in enhancing learning performance. In this research, a system to utilise both cloud materials and crowd intelligence is proposed and an experiment to validate the system is included.